Dreaming a Radical Citizenship: How Undocumented Queers in the United States Configure Sites of Belonging and Being through Art and Media Technologies - Ximena Keogh Serrano (European Journal of American Studies)
Following the Undocuqueer Movement’s practices of social visibility and activism, this article looks at the ways in which their artistic modes of self-inscription (be in the physical form or online circulation) produce alternative queer dwellings, and propose radical modes of belonging.